Sustainable Character Building: A Model for Integrating Coastal Islamic Values into Secondary Education - Nuzulul Afillah; Suni Amanah; Narti Anwarina; Raikhan Raikhan (STAI Syaichona Moh. Cholil Bangkalan, 2026)
This study aims to analyze the implementation of sustainability values within various educational activities at secondary education, encompassing intracurricular, extracurricular, and co-curricular programs. The scientific novelty lies in the development of a holistic integration model based on iman, ilmu, amal (faith, knowledge, practice) within the context of coastal Islamic education at secondary education. A descriptive qualitative approach was employed to explore how the principles of sustainability spiritual, social, cultural, and environmental are integrated into Islamic-based school activities. Data were collected through observation, documentation, and literature review. The findings reveal that intracurricular activities incorporate sustainability values through ecological responsibility, local resources, and green technologies. Extracurricular programs promote spiritual, social, and cultural sustainability. Co-curricular activities cultivate empathy and moral responsibility. Theoretically, this integration succeeds through a faith-based normative driver (khal?fah, amanah, i?s?n) that aligns moral identity with stewardship practices, strengthening intrinsic motivation for pro-environmental behavior. This study concludes that Islamic education holds great potential in fostering sustainable character development through a holistic approach, reinforcing Islamic schools as agents of social transformation toward sustainable development.